Letters of wisdom [large type] - Brunstetter, Wanda E. (The friendship letters, 2024)
"Doretta Schwartz has always enjoyed writing letters and feels her letters can be a bit of a ministry to her friends. In this series, exchanging letters that contain open and honest feelings and struggles helps Doretta and two of her best friends through the darkest challenges of their lives. Letters and Prayers Between Friends Become a Balm for Healing Irma Miller thought having a family of her own would bring her joy and a sense of accomplishment, but she struggles with memories of the abuse she suffered as a child at the hand of her stepfather. When she becomes physically and emotionally abusive to her own children, she reaches out to her friend Doretta for prayer and wisdom. But Irma may find herself at an even darker emotional place before she will admit she needs professional help to heal the past traumas. Will Doretta's letters of wisdom help Irma and her family, or will too much be broken to ever be repaired?"--